Evaluation of Various Factors Leading to Osteolytic and Antiosteolytic Effects in Patients With Rheumatoid Arthritis - Kazım Serkan SUNAL,; Ayşen CANİKLİOĞLU,; Hüseyin DEMİR,; Emre ERSOY,; Derya KOÇER,; Kıymet DOLBUN SEÇKİN,; Aysun ŞAHİN SUNAL,; Gülden BAŞKOL, (Archives of Rheumatology, 2015)
Objectives: This study aims to evaluate the biomarkers of bone formation and resorption to determine the mechanism of bone deformities in patients with rheumatoid arthritis (RA). Patients and methods: Thirty patients (9 males, 21 females; mean age, 51.5 years; range 23 to 73 years) with RA and 19 healthy individuals (7 males, 12 females; mean age 51 years; range 24 to 61 years) were included in this study. Patients with RA were subgrouped according to disease activity (active, n=21, mean age 53.0; range 37 to 73 years; inactive, n=9, mean age 46.0; range 23 to 62 years). Levels of receptor activator of nuclear factor kappa B ligand (RANKL), osteoprotegerin (OPG), tartrate-resistant acid phosphatase-5b, tumor necrosis factor-alpha (TNF-α), cathepsin-K, and activity of matrix metalloproteinase-3 (MMP-3) were measured in patient and control groups with enzyme-linked immunosorbent assay method. Results: Levels of RANKL, OPG, cathepsin-K, TNF-α and MMP-3 activities of the patients were significantly higher when compared with the controls (p<0.05). A comparison of the active and inactive patients with RA revealed that OPG levels and MMP-3 activities were significantly higher in active group than inactives (p<0.05), while there was no significant difference in TNF-α, RANKL levels, and tartrate-resistant acid phosphatase-5b and cathepsin-K activities between two groups (p>0.05). Conclusion: Increased RANKL, OPG, TNF-α, cathepsin-K levels and MMP-3 activities in RA patients demonstrated that these parameters are related to bone deformities which occur in the process of RA. Widespread use of these parameters may be beneficial for the early diagnosis and effective treatment of RA and similar diseases resulting in bone deformities in the future.